Hannah Arendt e Karl Jaspers: a culpa alemã - Tizzo, Fabiano Miranda do Nascimento (2022)
This work was developed based on the thinking of philosophers Karl Jaspers (1883 – 1969) and Hannah Arendt (1906 – 1975). It is an analysis of the vision of both with emphasis on the idea of “guilt” coined by Jaspers and on the “responsibility” thought by Arendt in the historical context experienced by the authors between 1945 and 1946. A dialogue was established from the perspective of both with regard to the crimes of totalitarianism in the post-war period (1939 – 1945) and with the consequent German defeat in the period. The peculiarity of each author's thinking was applied in order to broaden the reflections on our theme – the difficulties in pointing out those who collaborated directly and indirectly in favor of Nazism